Scanner for Dummies 2nd Edition - Chambers, Mark L. (Wiley Publishing, 2011)
Computer scanners now can do all that and more, and you don’t need a degree in the magical arts (in other words, a computer programming degree) to use one with your PC or Macintosh computer system. The facts get even better, too: The perfect scanner for most home and small business uses costs less than $150, and you can connect it and produce your first scanned image in less than five minutes. After all, the faster you get a picture of that ’79 Pinto on your Web site, the better the chance that you can finally unload it! this book introduce you to the computer equivalent of the alchemist’s magic box. You discover what you can do with a scanner, what types of scanners are available, what makes them tick (if you want to know), and the importance of resolution and color.